Kepemimpinan Kontigensi dan Implementasinya di Lembaga Pendidikan - Ahmad Turmuzi (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
Contingency is a theory about finding a leader with the right situation. Contingency leadership assumes that the effectiveness of leadership is determined by whether or not a leader is suitable for his environmental situation. The purpose of this study was to determine how the implementation of contingency leadership in educational institutions. The method used in this study is a library research where researchers examine and examine various existing sources to be used as studies in this study. The result of this research is that each leader will lead in a different way according to the existing situation and conditions. but there are three important things that must be applied by the leader, namely the relationship between the leader and members, the arrangement of the leader's duties to be carried out by the members, and the last is the strength of the position. These three things are things that a leader must have.